Pengaruh Pendapatan Asli Daerah (PAD) Dan Danaperimbangan Terhadap Kemandirian Keuangan Pemerintahan Daerah Di Kab. Pasaman Barat - Handraini, Helti; Frinaldi, Aldri; Asnil, Asnil; Putri, Nora Eka (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
West Pasaman, like many regions outside the main economic centers in Indonesia, relies heavily on transfers of funds from the central government through the Balancing Fund, which includes the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Profit Sharing Fund (DBH). ). This dependence shows that PAD, which should reflect regional capabilities in managing local resources, is still limited, so that regional fiscal conditions become vulnerable. This research analyzes the influence of low PAD and Balancing Funds on financial independence in West Pasaman Regency. Using a descriptive qualitative approach, this research describes and analyzes the influence of PAD and Balancing Funds on the financial independence of local governments. Data was collected through a review of literature studies including scientific journals, government reports and official documents. The analysis technique applied is document study to understand local government policies and their impacts. The research results show that West Pasaman's financial independence is hampered by dependence on the Balancing Fund, as well as weaknesses in governance, human resource capacity and infrastructure. However, there are opportunities to reduce dependency by diversifying income sources and optimizing local economic potential.